Production and application of O2 enriched air produced by fresh and salt water desorption in chemical plants. (1st July 2018) - Galli, F.; Previtali, D.; Bozzano, G.; Bianchi, C.L.; Manenti, F.; Pirola, C.
Abstract: Oxygen enriched air intensifies oxidation processes since smaller reactors reach the same conversion of typical unit operations that employ simple air as reactant. However, the cost to produce pure oxygen or oxygen enriched air with traditional methods, i.e. cryogenic separation or membrane technologies, may be unaffordable. Here, we propose a new continuous technology for gas mixture separation, focusing on the production of oxygen enriched air as a case study. This operation is an absorption-desorption process that takes advantage of the higher oxygen solubility in water compared to nitrogen. In a pressurized solubilisation tank, water absorbs air. Subsequently, reducing pressure desorbs oxygen enriched air. PRO/II 9.3 (Simsci-Scheider Electrics) simulated, optimized, and calculated the capital and operative expenses of this technology. Moreover, we tested for the first time salt water instead of distilled water as appealing possibility for chemical plant near sea and ocean. We varied the inlet water flowrate between 5 and 15 m 3 /h. The optimum operative absortion unit pressure is 15–35 barg. After degassing, water may be recycled. With salt water, the extracted quantity of enriched air decreases compared with the desorption from fresh water (20% less), while the concentration of oxygen is independent from the salt concentration. The cost of enriched air at the optimum condition is 2–3.35 EUR/Nm 3 . Highlights: Water degassing produces oxygen enriched air. Pressure variation is the driving force to obtain enriched air. We proposed and validated a thermodynamic approach to simulate salt water. An optimal pressure of the saturation tank has been identified. Salt water desorbs less air but the effect on its concentration is negligible.